AN AUDIT OF CONTINUOUS GLUCOSE MONITORING ON GLYCAEMIC CONTROL AND METABOLIC PROFILES OF PATIENTS WITH TYPE 1 DIABETES MELLITUS AT A TERTIARY CENTRE - Mok , Meng Loong; Valayatham, Vijiya Mala (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Type 1 Diabetes Mellitus (T1DM) is a chronic autoimmune disorder that results in absolute insulin deficiency and an elevated risk of both microvascular and macrovascular complications. Achieving optimal glycemic control is essential for preventing these complications. Continuous Glucose Monitoring (CGM) has been demonstrated to enhance glycemic control compared to conventional self-monitoring of blood glucose (SMBG). This audit aims to assess glycemic control and metabolic profiles among patients with T1DM at the Endocrine Institute, Putrajaya Hospital, comparing those using CGM with those relying on SMBG to determine whether CGM leads to improved metabolic outcomes. METHODOLOGY A retrospective cross-sectional study was conducted at the Endocrine Institute, Putrajaya Hospital. Electronic medical records of patients who attended the TIDM clinic between April 1, 2024, and March 31, 2025, were reviewed. Descriptive and statistical analyses of glycaemic control and metabolic profiles between CGM users and those using SMBG were performed using SPSS version 25. RESULT A total of 150 patients were included in the study. Overall, the population exhibited poor glycemic control and metabolic profiles, with a mean HbA1c of 9.0%. Additionally, 55% of the patients were overweight or obese. Seventy-one percent had elevated LDL-c levels (>2.6 mmol/L), with a mean LDL-c of 3.2 mmol/L. Of the patients, 24.7% used CGM for glycemic monitoring and had a significantly lower HbA1c (-1.2%) than the SMBG group. The study also demonstrated a significant reduction in HbA1c (-0.8%) after switching to CGM for monitoring. However, no significant differences were observed in BMI or LDL-c levels between the CGM and SMBG groups. CONCLUSION This study showed that the use of CGM contributed to better glycemic control in patients with T1DM. However, achieving optimal glycemic control alone is insufficient for effective weight management and improving lipid profiles. Therefore, lifestyle interventions, weight management strategies, and pharmacological treatments for lipid reduction are also necessary.